Genetic determinants of circulating estrogen levels and evidence of a causal effect of estradiol on bone density in men - Eriksson, Anna L.; Delgado Gonzales de Kleber, Graciela; Kleber, Marcus E. (The journal of clinical endocrinology & metabolism, 2018)
Objective: To investigate the genetic regulation of serum E2 and E1 in men. Design, Setting, and Participants: Genome-wide association study in 11,097 men of European origin from nine epidemiological cohorts. Main Outcome Measures: Genetic determinants of serum E2 and E1 levels. - Results: Variants in/near CYP19A1 demonstrated the strongest evidence for association with E2, resolving to three independent signals. Two additional independent signals were found on the X chromosome; FAMily with sequence similarity 9, member B (FAM9B), rs5934505 (P = 3.4 3 1028) and Xq27.3, rs5951794 (P = 3.1 3 10210). E1 signals were found in CYP19A1 (rs2899472, P = 5.5 3 10223), in Tripartite motif containing 4 (TRIM4; rs17277546, P = 5.8 3 10214), and CYP11B1/B2 (rs10093796, P = 1.2 3 1028). E2 signals in CYP19A1 and FAM9B were associated with bone mineral density (BMD). Mendelian randomization analysis suggested a causal effect of serum E2 on BMD in men. A 1 pg/mL genetically increased E2 was associated with a 0.048 standard deviation increase in lumbar spine BMD (P = 2.8 3 10212). In men and women combined, CYP19A1 alleles associated with higher E2 levels were associated with lower degrees of insulin resistance. - Conclusions: Our findings confirm that CYP19A1 is an important genetic regulator of E2 and E1 levels and strengthen the causal importance of E2 for bone health in men. We also report two independent loci on the X-chromosome for E2, and one locus each in TRIM4 and CYP11B1/B2, for E1. (J Clin Endocrinol Metab 103: 991-1004, 2018)